EKESIOLOGI DI ERA KECERDASAN BUATAN: REFLEKSI TEOLOGIS ATAS IDENTITAS DAN MISI GEREJA DIGITAL - Limbong, Sukanto (Publisher: Bethel Press; Unit Penerbit: STT Bethel Indonesia Jakarta, 2025)
Technological developments, particularly artificial intelligence (AI), are transforming human life, including in the context of the church. This article examines the relevance and identity of the church in the AI era using a biblically based theological approach, specifically the human cultural mandate (imago Dei) and the warning against human pride (the Tower of Babel). This research uses qualitative methods through literature study and biblical analysis. The results show that AI can expand mission reach, increase efficiency, and personalize ministry, but also raise theological and ethical challenges, such as dehumanization, algorithmic bias, and the risk of degradation of personal relationships. The essence of the church as a relational community living in the love of Christ, as well as the sacraments and the role of the pastor, remain irreplaceable. This article provides a new reflective-theological framework for understanding AI as a strategic opportunity without obscuring the essence of the church, thus contributing to the development of digital ecclesiology discourse in the context of contemporary theology.